Pervasive yet nonuniform contributions of Dcp2 and Cnot7 to maternal mRNA clearance in zebrafish. (30th May 2017) - Mishima, Yuichiro; Tomari, Yukihide
Abstract : mRNA degradation is a fundamental biological process that erases transcribed genetic information from cells. During maternal‐to‐zygotic transition of animal development, thousands of maternal mRNAs are degraded by multiple mechanisms including microRNAs and codon‐mediated decay. Enzymatic requirements for maternal mRNA clearance, however, are not fully understood. Here, we analyzed a contribution of the decapping enzyme Dcp2 to maternal mRNA clearance in zebrafish by over‐expressing catalytically inactive Dcp2 and performing RNA‐seq analysis. As expected, Dcp2 had a widespread role in maternal mRNA clearance. Interestingly, each mRNA showed differential dependency on Dcp2‐mediated decapping and Cnot7‐mediated deadenylation for degradation. Correlation analysis identified several mRNA features that were associated with the observed differential dependency. Our results show pervasive yet nonuniform contributions of the decapping enzyme Dcp2 and the deadenylase Cnot7 to maternal mRNA clearance. Abstract : mRNA degradation is a fundamental biological process that erases transcribed genetic information from cells. In this study, the authors analyzed contributions of a decapping enzyme Dcp2 and a deadenylase Cnot7 to maternal mRNA clearance in zebrafish.